Learner’s autonomy in an undergraduate English flipped course - Al Wahaibi, Suad Saleh; Hashim, Sulaiman (Centre for Promoting Knowledge (CPK), UK., 2018)
The main purpose of the present study is to examine the extent to which flipping an English course affected students’ autonomy compared to the traditional approach. The study took place at the Center for Preparatory Studies at Sultan Qaboos University in the educational year 2016/2017. The study involved two groups studying a foundation English course, sixteen students in the control group and seventeen in the experimental. The study employed a triangulation mixed methods research design where quantitative and qualitative data were collected at the same time and then combined to interpret the overall results. The quantitative data was collected through a Learner Autonomy Questionnaire and system logs. The qualitative data, on the other hand, was collected through teacher’s interview. The results for the LAQ and system logs revealed that there were statically significant differences in favor of the experimental group (U = 24.5, p= 0.000 < 0.05, r= 0.69 and U = 35.5, p= 0.000 < 0.05, r= 0.62 respectively). The qualitative data collected through interviewing the teacher of the two groups involved in the study revealed that the experimental group was more autonomous than the traditional one. All results from the three tools used to examine learner autonomy were in favor of the experimental group as the experimental group was found to be more autonomous than the control group. The study ends up with some implications and recommendations for future research.